Algorithms for the Generation of an Electronic Customized Answer Booklet for Universities - Doreck Nduhukire; Evarist Nabaasa; Deborah Natumanya (Indonesian Journal of Innovation and Applied Sciences (IJIAS), 2023)
Academic institutions in Uganda are accustomed to using pen-on-paper exams where students are given an answer booklet at the time of the exam. Universities frequently use customized answer booklets which help to lower the prevalence of exam fraud among students. Universities continue to encounter the challenge of examining summative questions like essays after the migration to electronic examinations brought about by the Covid-19 social distancing effects due to the lack of a customized electronic answer booklet. The primary goal of this research was to design algorithms for a customized electronic answer booklet. These algorithms went through six stages, starting with analyzing the problem and ending with developing the algorithms. The design, analysis, and coding of four algorithms i.e. cover page, single empty page, adding a page, and watermark addition algorithms was completed. The designed electronic personalized answer booklet is dynamic in nature and supports page addition, text crossing out or rubbing, and navigating through the electronic question paper. Any academic institution may utilize this electronic answer book.